A review of a newly established ECMO program in a university affiliated cardiac center - Belohlávek, J; Rohn, V; Tosovsky, J; Kunstyr, J; Semrád, M; Horák, J; Lips, M; Mlejnsky, F; Vykydal, I; Balík, M; Strítesky, M; Mrázek, V; et al. (The Journal of cardiovascular surgery, 2011)
Extracorporeal membrane oxygenation (ECMO) is an established rescue treatment option for severe respiratory and cardiac failure in infants and neonates and has recently become widely utilised in adults. ECMO support can be initiated rapidly in an emergency setting both by percutanous implantation and surgically; it allows transportation of patients in cardio-pulmonary collapse and bridging of critically ill patients to be recovered, other support measures or transplantation. The aim of this study was to report authors' initial experience after starting an ECMO program in a university-based cardiac center. The institutionally approved ECMO team bears responsibility for adjudication regarding indication and implementation of ECMO in all patients. Since the establishment of the ECMO team in October 2007, one elective and nine urgent patients in deep cardiogenic and/or ventilatory collapse were treated by ECMO support up to December 2008. Three patients suffered severe acute right heart dysfunction, two patients suffered postcardiotomy refractory cardiogenic shock, two patients had a cardiogenic shock due to postinfarction interventricular septal rupture, two patients experienced severe respiratory failure and one had elective ECMO implantation as a back-up support during high-risk percutaneous coronary intervention. Veno-arterial ECMO was used in eight cases and veno-venous in two cases of isolated respiratory failure. In nine patients, ECMO circuit was instituted by peripheral cannulation, in eight out of nine cases by percutaneous puncture. On one occasion central surgical cannulation was used. In urgent patients, immediate hemodynamic and oxygenation improvement was observed. Average support duration was 6.8 days (range 1-16 days). Five (50 %) patients were successfully weaned from ECMO and survived to hospital discharge. The illness severity in urgent patients defined by SOFA score ranged from 10 to 17, patients dying while on ECMO had higher SOFA scores (14.8±1.6 vs. 10.8±1.5; P=0.0065). Complications included mainly bleeding. ECMO support allows treatment of severely ill patients in imminent cardiovascular and/or ventilatory collapse. Therefore, establishment of an ECMO program in university affiliated cardiac center is fully justified. A multidisciplinary approach is essential. Despite adequate training and education of ECMO team members, this highly invasive therapeutic modality bears an inherent risk of complications.
Keywords: dospělí; Extracorporeal Membrane Oxygenation; mimotělní membránová oxygenace; Female; kritický stav; Adult; výsledek terapie; ženské pohlaví; mortalita v nemocnicích; týmová péče o pacienty; Time Factors; časové faktory; lidé; Program Evaluation; nemocnice fakultní; Heart Diseases; Treatment Outcome; Respiratory Insufficiency; stupeň závažnosti nemoci; Humans; hodnocení programu; Male; Aged; Czech Republic; Patient Care Team; Česká republika; Hospital Mortality; Hospitals, Teaching; lidé středního věku; senioři; mužské pohlaví; Severity of Illness Index; Middle Aged; respirační insuficience; Critical Illness; nemoci srdce